Ailing Screens, Viral Video: Cinema's Digital Ghosts in Kiyoshi Kurosawa's Pulse. - Hughes, Kit (Film Criticism)
The article offers criticism on the 2001 Japanese film "Pulse," originally released as "Kairo" in Japan, directed by Kiyoshi Kurosawa. The author focuses on ghosts and technology in the film and discusses the relationship between ghosts and recording technology. Specific topics include alienation and isolation as the result of technology in the film, four categories of ghostly moments in the film including emptied frames, and the J-Horror genre of Japanese horror films.